2014
DOI: 10.1103/physrevb.89.014105
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation networks in4He crystals

Abstract: The mechanical behavior of crystals is dominated by dislocation networks, their structure and their interactions with impurities or thermal phonons. However, in classical crystals, networks are usually random with impurities often forming non-equilibrium clusters when their motion freezes at low temperature. Helium provides unique advantages for the study of dislocations: crystals are free of all but isotopic impurities, the concentration of these can be reduced to the ppb level, and the impurities are mobile … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
72
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 36 publications
13
72
1
Order By: Relevance
“…If in the case of point defects it can be said that theory has led the way to their (partial) understanding, in the case of dislocations is the other way around. At present, most of what we know about dislocations in quantum solids comes from recent experiments performed by the groups of Beamish, in the University of Alberta, and Balibar, in the Ecole Normale Supérieure de Paris (see, for instance, Haziot et al, 2013a;Haziot et al, 2013b;Fefferman et al, 2014;Souris et al, 2014a). Such a gap between theory and experiments is due to several reasons.…”
Section: B Dislocationsmentioning
confidence: 99%
See 2 more Smart Citations
“…If in the case of point defects it can be said that theory has led the way to their (partial) understanding, in the case of dislocations is the other way around. At present, most of what we know about dislocations in quantum solids comes from recent experiments performed by the groups of Beamish, in the University of Alberta, and Balibar, in the Ecole Normale Supérieure de Paris (see, for instance, Haziot et al, 2013a;Haziot et al, 2013b;Fefferman et al, 2014;Souris et al, 2014a). Such a gap between theory and experiments is due to several reasons.…”
Section: B Dislocationsmentioning
confidence: 99%
“…They found that µ increased with decreasing T below a certain temperature of 0.15 K. The observed increase in stiffness was rationalised in terms of line defects mobility: below a particular temperature threshold the dislocations present in the crystal could be pinned by 3 He impurities, in spite of the incredibly small concentration of the latter (i. e., just 200 parts per billion of 4 He atoms). This argument has been subsequently ratified by a number of compelling experimental works carried out by the groups of Beamish, in the University of Alberta, and Balibar, in the Ecole Normale Supérieure de Paris (see, for instance, Haziot et al, 2013a;Haziot et al, 2013b;Fefferman et al, 2014;Souris et al, 2014a). Remarkably, Haziot et al (2013c) have recently shown that in ultra-pure single crystals of 4 He the resistance to shear along one particular direction nearly vanishes at around T = 0.1 K, whereas normal elastic behavior is observed in the others.…”
Section: Incomplete Understanding Of Quantum Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparable change for helium in Vycor would change the system's transverse sound speed by about 0.2 %. However, the shear modulus changes in bulk 4 He are due to the motion of dislocations which can glide very easily in the basal plane of hcp 4 He [14][15][16][17]. At high frequencies these dislocations are strongly damped by thermal phonons, which greatly reduces their effects on elastic constants.…”
Section: Introductionmentioning
confidence: 99%
“…At low dislocation speeds and low temperatures, 3 He impurities bind to the dislocations and move with them, damping their vibrations [3]. The binding energy E B was determined from the frequency dependence of the peak dissipation temperature under the assumption that the damping due to 3 He is proportional to the concentration of 3 He atoms bound to the dislocations [3,5,7]. In order to test this assumption, we are measuring the 3 He damping coefficient as a function of the 3 He concentration in the helium gas that we use to grow our crystals.…”
Section: Introductionmentioning
confidence: 99%